Evaluation of community-based disease surveillance systems for priority disease detection in Nairobi County Kenya - Muange, Annastacia Katuvee; Kariuki, John; Mwitari, James (International Journal Of Community Medicine And Public Health, 2021)
Background: Community based disease surveillance (CBDS) may be defined as an active process of community involvement in identification, reporting, responding to and monitoring diseases and public health events of concern in the community. The scope of CBS is limited to systematic continuous collection of health data on events and diseases guided by simplified lay case definitions and reporting to health facilities for verification, investigation, collation, analysis and response as necessary. Methods: A cross sectional study design, interventions study program was adopted to determine the effectiveness of CBDS in detecting of priority diseases. Purposive and random sampling methods was employed to select the respondents. Results: The results of the study assisted the Ministry of health to understand the effectiveness of Community based surveillance in detection of priority diseases and hence strengthen the community-based surveillance initiative. From the findings, the integrated disease surveillance data for five years from 2014-2018 shows, more cases of priority diseases reported in health facilities linked to a community unit trained on CBDS. Cholera (9/5), Malaria (4757/2789), Neonatal tetanus (27/3) respectively. Conclusions: The study concluded that, use of community-based surveillance system, improves detection of the notifiable diseases in the community. The study revealed that there is a gap on training of community-based disease surveillance system and therefore there is need for continuous refresher trainings on CBDS to the CHVs and CHAs to accommodate also the newly recruited.